The association between urinary tract infection during pregnancy and preeclampsia: A meta-analysis. Issue 36 (September 2018) - Yan, Ling; Jin, Yu; Hang, Hongdong; Yan, Bin
Abstract: Objective: The association between urinary tract infection (UTI) during pregnancy and preeclampsia (PE) continues to be the subject of debate. This meta-analysis aimed to examine the relationship between UTI during pregnancy and PE. Study design: Observational studies up to October 2017, extracted from Medline, PubMed, Cochrane Library, and Embase databases, were included in the analysis. Data were extracted to 4-fold table, and the pooled odds ratio (OR) and 95% confidence intervals (CIs) of respective studies were calculated. Then meta-analysis was performed. Results: Nineteen studies qualified the inclusion criteria. Urinary tract infection during pregnancy was found to be a risk factor for the development of PE (OR: 1.31, 95% CI: 1.22–1.40). Conclusion: Occurrence of UTI during pregnancy increases the risk of PE in pregnant women. Screening for, and treatment of UTI should be part of routine antenatal care, especially in developing countries. Abstract : Supplemental Digital Content is available in the text